(untitled) (Journal of the College of Basic Education, 2025)
This research aims to evaluate the website of the General Traffic Directorate - Fines page by using one of the website evaluation tools, which is (SORT site). The analysis process revealed the presence of errors in the programming language of the database page related to the repetition of the ID for more than one item in line( 550) of the fines page. In addition, the database works well but needs to be updated quickly, as the last update dates back to 4/3/2021. In addition, there is a need to overcome the programming problem in the language regarding giving the same ID to many items. The research came out with a recommendation stipulating the necessity of adding the auto-complete feature in order for the page to work optimally, and in line with the requirements of the WCAG standards in the part of completing the knowledge deficiency for some in case they face difficulty in searching within the traffic fines database.